2008
DOI: 10.1021/jf8018529
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Composition of Wild Bananas in Thailand

Abstract: Anthocyanins were isolated from male bracts of 10 wild species of bananas (Musa spp. and Ensete spp.) distributed in Thailand. Six major anthocyanin pigments were identified by high performance liquid chromatography (HPLC), mass spectrometry (MS), and tandem mass spectrometry (MS/MS). They are delphinidin-3-rutinoside (m/z 611.2), cyanidin-3-rutinoside (m/z 595.8), petunidin-3-rutinoside (m/z 624.9), pelargonidin-3-rutinoside (m/z 579.4), peonidin-3-rutinoside (m/z 608.7), and malvidin-3-rutinoside (m/z 638.8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Another similar study showed that NO treatment significantly enhanced flavonoid contents in the mushrooms and the antioxidant activities in the NO-fumigated mushrooms were highly correlated with the contents of flavonoids (Dong et al, 2012). Study has shown that anthocyanins are the largest and most important group of water-soluble and vacuolar pigments in nature (Cavalcanti et al, 2011) and it have been identified in wild banana bracts (Kitdamrongsont et al, 2008). In the present study, the major free soluble flavonoid was cyanidin-3- O -glucoside chloride in banana pulp.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar study showed that NO treatment significantly enhanced flavonoid contents in the mushrooms and the antioxidant activities in the NO-fumigated mushrooms were highly correlated with the contents of flavonoids (Dong et al, 2012). Study has shown that anthocyanins are the largest and most important group of water-soluble and vacuolar pigments in nature (Cavalcanti et al, 2011) and it have been identified in wild banana bracts (Kitdamrongsont et al, 2008). In the present study, the major free soluble flavonoid was cyanidin-3- O -glucoside chloride in banana pulp.…”
Section: Discussionmentioning
confidence: 99%
“…The anthocyanins, a subclass of flavonoids are an important pigment group that is responsible for the red, purple, and violet colors of the banana inflorescence (Kitdamrongsont et al 2008). Anthocyanins are considered to be a good biocolorant due to its attractive colors, moderately stable in food systems, water-soluble (Ozela et al 2007;Torslangerpoll and Andersen 2005), and proven to be beneficial to health (Bagchi et al 2004;Konzack and Zhang 2004).…”
Section: Natural Bio-colorantmentioning
confidence: 99%
“…Besides, anthocyanins also possessed anti-inflammatory (Bowen-Forbes et al 2010;Karlsen et al 2007), antiviral (Wang et al 2006), anticarcinogenic (Kulma and Szopa 2007), antiproliferative effect (Mokbel and Hashinaga 2005), and cancer chemoprevention properties (Bowen-Forbes et al 2010;Wang et al 2011). Banana inflorescence from either cultivated and wild varieties are rich in anthocyanins (Jenshi Roobha et al 2011;Kitdamrongsont et al 2008) suggest it could potentially serves as a source of functional food components which are beneficial to health.…”
Section: Source Of Nutraceutical and Bioactive Compoundsmentioning
confidence: 99%
“…Previous research on preliminary phytochemcial screening of dried leaves and fruit peels of Musa paradisiaca revealed the presence of some glycosides, anthnocyanins, tannins, flavanoids and carbohydrates [6]. No research has been reported on the phytochemical screening of banana flowers except a quantitative study on saponin and flavanoid [7] and later phenolic content by Loganayaki et al [8]. The bract part of Musa paradisiaca was reported to contain anthocyanins such as delphinidin, pelaragonidin, peonidin and malvidin [9,10].…”
Section: Properties and Applications Of Musa Acuminata Bractmentioning
confidence: 99%